Furry Futures: Can China's New Pet Science Program Match Industry Hype? (Beijing Review, 2025)
The article discusses the burgeoning night market economy in Beijing during the summer months, highlighting how residents are increasingly seeking evening markets for dining, shopping, and entertainment to escape the daytime heat. Notable markets include established ones like Guijie and Sanlitun, as well as newer, popular venues such as Yuelianghe and Panjiayuan. Additionally, the article mentions the launch of China's first undergraduate program in companion animal science at China Agricultural University (CAU), aimed at addressing the growing demand for pet-related professionals in a rapidly expanding pet industry. The program is designed to provide students with a comprehensive education in areas such as breed genetics and animal welfare, preparing them for various careers in the pet sector.